The future of superconducting microcircuits for widefield Imaging at submillimetre wavelengths - Withington, S; Yassin, G (2001)
Superconducting detectors are set to become the principal method by which wide-field mapping and deep point-source searches are carried out throughout the whole of the submillimetre-wave frequency range. In the paper, we outline the operation of the basic detector types, and assess the future of superconducting detector technology. We place particular emphasis on distinguishing between single-mode, few-mode, and multi-mode designs, and we explain how similar the superconducting bolometer and mixer technologies have become. We outline the considerable advances that are taking place in the area of superconducting detector technology.